IMPLEMENTASI AKUNTANSI GUNA MEMBERDAYAKAN UMKM DI KECAMATAN SEMAMPIR (Studi Kasus Pendampingan Legalitas UMKM dalam rangka pemberdayaan UMKM menuju naik kelas) - Aisyah Rahma Naura; Dyah Ratnawati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research focuses on the importance of accounting implementation and legality assistance in empowering Micro, Small, and Medium Enterprises (MSMEs) in Semampir District. Accounting is an important tool for recording, managing, and reporting financial information that enables MSMEs to monitor financial health, make informed decisions, and ensure transparency and accountability. Business legality, such as ownership of a Home Industry Product Permit (PIRT) and Business Identification Number (NIB), also plays a crucial role in accessing financing, increasing credibility, and utilizing government programs.